A parallel FFT‐accelerated layered‐medium integral‐equation solver for electronic packages. (10th September 2019) - Liu, Chang; Aygün, Kemal; Yılmaz, Ali E.
Abstract: A parallel iterative layered‐medium integral‐equation solver is presented for fast and scalable network parameter extraction of electronic packages. The solver, which relies on a 2‐D fast Fourier transform (FFT)‐based algorithm and a sparse preconditioner to reduce computational complexity, is parallelized using three workload decomposition strategies, including a pencil decomposition that increases the scalability of the computationally dominant FFT‐based multiplication stage. A set of increasingly difficult benchmark problems, which require network parameter computations for N trace = 1 to 257 package‐scale interconnects, are solved on a petaflop scale computer to quantify the solver's accuracy, efficiency, and scalability. The total serialized computation time is observed to scale asymptotically as N trace 2.6 log N trace . For the largest problem, using 1.14 million unknowns and 1536 processes, the solver requires a wall‐clock time of 0.05 s per iteration, 1 minute per excitation, 9 h per frequency, and 424 hours to extract the 514‐port network parameters at 40 sample frequencies between 1 to 40 GHz.